Broadening participation in STEM : effective methods, practices, and programs - Wilson-Kennedy, Zayika S.; Byrd, Goldie S.; Kennedy, Eugene, 1955-; Frierson, Henry T. (Henry Taylor), 1944- (Diversity in higher education, 2019)
This book reports on high impact educational practices andprograms that have been demonstrated to be effective at broadening theparticipation of underrepresented groups in the STEM disciplines.